Analysis of the polymorph changes of a drug candidate - Langó Péter; Várkonyi E.; Ulrich Joachim; Révész Piroska; Aigner Zoltán (2015)
The effects of solvents, temperature and humidity on the stability of a former drug candidate obtained from Sanofi (Hungary) were examined by a slurry equilibration method, variable temperature and humidity X-ray powder diffractometry (VT/VH-XRPD) and differential scanning calorimetry (DSC). The VH-XRPD study showed that all 8 polymorphic forms of this material were stable in the interval 20-80 RH%. The VT-XRPD measurements indicated that all the polymorphs except Form II underwent changes in the range 30-200 degrees C. The stable form was Form II, though Form IVb had almost the same stability. The investigation demonstrated that VT-XRPD is a very useful in situ method for relative stability studies.